Measurements of Propanal Ignition Delay Times and Species Time Histories Using Shock Tube and Laser Absorption. Issue 11 (18th July 2016) - Koroglu, Batikan; Vasu, Subith S.
ABSTRACT: Propanal is an aldehyde intermediate formed during the hydrocarbon combustion process. Potentially, the use of oxygenated biofuels reduces greenhouse gas emissions; however, it also results in increased toxic aldehyde by‐products, mainly formaldehyde, acetaldehyde, acrolein, and propanal. These aldehydes are carcinogenic, and therefore it is important to understand their formation and destruction pathways in combustion systems. In this work, ignition delay times were measured behind reflected shock waves for stoichiometric (Φ = 1) mixtures of propanal (CH3 CH2 CHO) and oxygen (O2 ) in argon bath gas at temperatures of 1129 K < T < 1696 K and pressures around 1 and 6 atm. Measurements were conducted using the kinetics shock tube facility at the University of Central Florida. Current results were compared to available data in the literature as well as to the predictions of three propanal combustion kinetic models: Politecnico di Milano (POLIMI), National University of Ireland at Galway, and McGill mechanisms. In addition, a continuous wave‐distributed feedback interband cascade laser centered at 3403.4 nm was used for measuring methane (CH4 ) and propanal time histories behind the reflected shock waves during propanal pyrolysis. Concentration time histories were obtained at temperatures between 1192 and 1388 K near 1 atm. Sensitivity analysis was carried for both ignition delay time and pyrolysis measurements to reveal the important reactions that were crucial to predicting the current experimental results. Adjustments to the POLIMI mechanism were adopted to better match the experimental data. Further research was suggested for the H abstraction reaction rates of propanal. In addition to extending the temperature and pressure region of literature ignition delay times, we provide the first high‐temperature species concentration time histories during propanal pyrolysis.